2020
DOI: 10.1371/journal.pone.0232033
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin promotes growth and sucrose metabolism of grape seedlings

Abstract: Melatonin (MT) has many important functions in plants. In this study, different concentrations of MT (0, 50, 100, 150, and 200 μmol/L) were sprayed on grape seedlings, and its effects on plant growth and sucrose metabolism were determined. The results show that there was a mutual influence and promotional relationship between growth and sugar metabolism in grape seedlings. The MT treatments promoted the development and growth of grape seedlings by increasing their biomass and promoting the photosynthetic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 47 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…In addition to being involved in defense responses, melatonin is also involved in plant growth in conjunction with photosynthesis when plants were challenged with abiotic stresses [ 20 , 56 ]. For example, melatonin treatment enhanced soybean growth by increasing PSI- and PSII-related genes and increased the rate of photosynthesis in Chinese hickory and grape seedlings upon stresses [ 57 , 58 , 59 ]. Melatonin treatment in tomato seedlings increased PSII activity and the photochemical quenching coefficient against salt stress [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being involved in defense responses, melatonin is also involved in plant growth in conjunction with photosynthesis when plants were challenged with abiotic stresses [ 20 , 56 ]. For example, melatonin treatment enhanced soybean growth by increasing PSI- and PSII-related genes and increased the rate of photosynthesis in Chinese hickory and grape seedlings upon stresses [ 57 , 58 , 59 ]. Melatonin treatment in tomato seedlings increased PSII activity and the photochemical quenching coefficient against salt stress [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that high doses of melatonin inhibit seedling growth by inducing the excessive accumulation of sucrose, hexose and starch, suppressing photosynthesis and sucrose phloem loading [ 76 ]. The role of melatonin in improving sucrose biosynthesis was also confirmed in pear, grape, and rice plants [ 70 , 79 , 80 ].…”
Section: Regulatory Action Of Melatonin On Carbohydrate Metabolismmentioning
confidence: 97%
“…In this present work, under salt stress or not, seedlings treated with 0.05 mM MT did not show increase or decrease in the plant growth parameters compared with mild salt-stressed plants or well-watered seedlings. In a recent work, Zhong et al (2020) concluded a benefit effect of 0.15 mM MT on grape seedling growth. Seedlings treated with 0.1 mM MT showed better effect on the growth traits of D. odorifera seedlings compared with 0.05 mM MT-treated and well-watered plants.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that exogenous application of MT or GB increases antioxidant enzyme activities under abiotic stress. In grape seedling leaves, exogenous MT treatment can significantly increase the CAT, SOD, and POD activities ( Zhong et al, 2020 ). Exogenous application of GB can increase the activities of SOD, CAT, APX, or POD in wheat leaves against drought and salinity ( Ma et al, 2006 ; Raza et al, 2007 , 2014 ) as well as in Glycine max against salt stress ( Malekzadeh, 2015 ).…”
Section: Discussionmentioning
confidence: 99%